Efektivitas Pembelajaran Realistic Mathematics Education (RME) terhadap Kemampuan Berpikir Kritis Siswa SMP - Nur Ainun Siti Fadilah; Dori Lukman Hakim (Peneliti.net, 2022)
This research is motivated by the importance of Realistic Mathematics Education learning in mathematics learning. This research was conducted at SMPN 1 Lemahabang class VII. The purpose of this study is to determine the effectiveness of learning by using Realistic Mathematics Education learning in learning mathematics. The results showed that by applying Realistic Mathematics Education (RME) learning, it could make a significant contribution to students' critical thinking skills. statistically there is a difference in value between the control class and the experimental class. Thus it can be concluded that RME learning is one of the effective learning models that can be used in learning.